2012
DOI: 10.1089/neu.2011.2027
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cervical Spinal Cord Injury: DTI Correlates with Clinical and Electrophysiological Measures

Abstract: Diffusion tensor imaging (DTI) is rarely applied in spinal cord injury (SCI). The aim of this study was to correlate diffusion properties after SCI with electrophysiological and neurological measures. Nineteen traumatic cervical SCI subjects and 28 age-matched healthy subjects participated in this study. DTI data of the spinal cord were acquired with a Philips Achieva 3 T MR scanner using an outer volume suppressed, reduced field of view (FOV) acquisition with oblique slice excitation and a single-shot EPI rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
93
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 47 publications
14
93
1
Order By: Relevance
“…Few reports about the diffusion properties of the spinal cord in the chronic state of the injury have been published in the literature. [11][12][13] In those studies, DTI has been shown to estimate the total lesion load in the spinal cord better than conventional MRI. FA values have been proven to diminish in areas of the intact upper spinal cord after injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports about the diffusion properties of the spinal cord in the chronic state of the injury have been published in the literature. [11][12][13] In those studies, DTI has been shown to estimate the total lesion load in the spinal cord better than conventional MRI. FA values have been proven to diminish in areas of the intact upper spinal cord after injury.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest secondary degeneration of the white matter tracts in the spinal cord. [11][12][13] Previously, abnormalities in DTI values of the cerebral corticospinal tract after SCI have also been reported. However, these studies consisted of relatively small samples and primarily included subjects with complete SCI.…”
Section: Introductionmentioning
confidence: 98%
“…For example, lower DTI parameters correlated with the clinical completeness of SCI and with SSEP amplitudes. 12 ASIA motor scores were correlated with DTI parameters in nonhemorrhagic SCI patients. 11 Although abnormal cervical levels detected on routine MRI did not correlate with clinical findings and DTI parameters, FAs on DTI correlated with motor function, as did the numbers of imaginary crossing fibers and the rates of connection of fiber tracks in patients with cervical SCI.…”
Section: Evoked Potentialsmentioning
confidence: 99%
“…Additional studies with more patients are needed to establish these correlations. Although previous studies 11,12,23 included patients with metal implants, the MRI signals around the implants might be altered, leading to image deterioration. Such deterioration is more severe in patients with posterior versus anterior implant fixation.…”
Section: Evoked Potentialsmentioning
confidence: 99%
See 1 more Smart Citation